Impact of psychiatric and social characteristics on HIV sexual risk behavior in Puerto Rican women with severe mental illness - Goldman Heaphy, Emily Lenore (2009)
BACKGROUND: Latinos in the United States have been identified as a high-risk group for depression, anxiety, and substance abuse. HIV/AIDS has disproportionately impacted Latinos. Review findings suggest that HIV-risk behaviors among persons with severe mental illness (SMI) are influenced by a multitude of factors including psychiatric illness, cognitive-behavioral factors, substance use, childhood abuse, and social relationships. OBJECTIVE: To examine the impact of psychiatric and social correlates of HIV sexual risk behavior in Puerto Rican women with SMI. METHODS: Data collected longitudinally (from 2002 to 2005) in semi-structured interviews and from non-continuous participant observation was analyzed using a cross-sectional design. Bivariate associations between predictor variables and sexual risk behaviors were examined using binary and ordinal logistic regression. Linear regression was used to examine the association between significant predictor variables and the total number of risk behaviors the women engaged in during the 6 months prior to baseline. RESULTS: Just over one-third (35.9%) of the study population (N = 53) was diagnosed with bipolar disorder and GAF scores ranged from 30 to 80 with a median score of 60. Participants ranged in age from 18 to 50 years (M = 32.6 ± 8.7), three-fourths reported a history of either sexual or physical abuse or of both in childhood, and one-fourth had abused substances in their lifetimes. Bivariate analyses indicated that psychiatric and social factors were differentially associated with sexual risk behaviors. Multivariate linear regression models showed that suffering from increased severity of psychiatric symptoms and factors and living below the poverty line are predictive of engagement in a greater number of HIV sexual risk behaviors. PRACTICAL IMPLICATIONS: Puerto Rican women with SMI are at high risk for HIV infection and are in need of targeted sexual risk reduction interventions that simultaneously address substance abuse prevention and treatment, childhood abuse, and the indirect effects associated with SMI such as living in poverty. Mental health programs should address risk behavior among adults with SMI in the context of specific symptomatology and comorbidities.